A Basic Strategy to Manage Global Health with Reference to Livestock Production in Asia - David C. Hall; Quynh Ba Le (Veterinary Medicine International)
Newly emerging infectious diseases (nEIDs) have increased rapidly presenting alarming challenges to global health. We argue that for effective management of global health a basic strategy should include at least three essential tactical forms: actions of a directly focused nature, institutional coordination, and disciplinary integration in approaches to health management. Each level of action is illustrated with examples from the livestock sector in Asia. No clear example of all three tactical forms in place can be found from developing countries where food security is a significant threat although Vietnam is developing a comprehensive strategy. Finally, an ecosystem health approach to global health management is advocated; such an approach moves away from the traditional single disciplinary approach. Stronger guidance is needed to direct ecohealth research and application in the management of global health.